Pengaruh Rekrutmen dan Pengembangaan Karir terhadap Kinerja Pegawai Pada Kantor DPRD Provinsi Sumatera Selatan - Selly Mariska; Hamid Halin; Meilin Veronica (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The study analyzed the impact of recruitment and career development on employee performance in the Regional House of Representatives (DPRD) Office of South Sumatera Province. A quantitative approach was used, and data were collected through the distribution of questionnaires to 76 respondents. The data were analyzed using multiple linear regression, classical assumption tests, t-test, and F-test. The research findings indicate that recruitment has a significant positive effect on employee performance, with a significance value of 0.041. Similarly, career development also has a significant positive effect on employee performance, with a significance value of 0.000. Furthermore, both recruitment and career development together have a significant positive effect on employee performance, with a significance value of 0.000. The coefficient of determination analysis reveals that the variables of recruitment and career development explain 23.4% of the variance in employee performance, while the remaining 76.6% is influenced or explained by other variables beyond the scope of this study